Carnivory submerged: aspects of the ecology and ecophysiology of the aquatic Utricularia stellaris L. fil. (Lentibulariaceae) in South Africa - Marais, Alice-Jane (Rhodes University, Faculty of Science, Botany Department)
The trapping structures produced by aquatic species of Utricularia have traditionally been interpreted to function as adaptations to capture and break down zooplankton prey, as in other carnivorous plants, to overcome nutrient limitations. However, an increasing number of studies have found that these plants may also rely on benefits derived from living mutualistic microbial communities contained within traps. This study documents aspects of the environmental, growth and physiological characteristics of U. stellaris to inform and to form a basis for future investigation into the plant-microbe interaction. The environmental conditions in which U. stellaris grows were documented to identify potential adverse conditions plants are subject to in situ, from which nutrient limitation was identified as a primary limitation. Plant growth and trapping structures were then assessed to identify possible adaptations of plants to overcome these limitations. The production of trapping structures likely constitutes an adaptive trait, with 30% of total biomass per node allocated to the production of these structures. Based on their capture function, traps may aid plants based on their contents, possibly supplementing plants with nutrients. Although assessments of the habitats of U. stellaris indicate that dissolved CO₂ concentrations in the ambient water are high, CO₂ may still be limiting to the photosynthetic rates of these plants due to viscous water resisting the diffusion of CO₂. The primary site of photosynthesis in U. stellaris is leaves and trap tissue's contribution to photosynthetic output is negligible. U. stellaris plants are subject to CO₂ limitations in natural pond conditions, making the substantial allocation of resources to non-photosynthetic trapping tissue even more costly. Therefore, benefits gained from trapping structures are likely to be derived from trap contents; having ruled out the possibility that the trap tissue itself is photosynthetic. Trap contents of U. stellaris were assessed. The proportion of traps containing living microbial communities greatly exceeded the proportion containing zooplankton prey. In addition, these communities were found to be diverse, stable, and self-sustaining. These results suggest that trapping structures may be beneficial for both the carnivorous capture of prey and the housing of living microbial communities. These results indicate the plantmicrobe interaction in U. stellaris warrants further study.
Keywords: Submerged aquatic vegetation; Bladderworts -- South Africa; Carnivorous plants; Bladderworts Ecology; Bladderworts Ecophysiology; Plant-microbe relationships